Evaluation of Surfactant Performance in Coal Dust Suppression for Underground Coal Mines - Zhao, Zidong (Curtin University, 2023)
The research provides a comprehensive study about selecting proper surfactants for coal dust control, identifying impacting factors of suppression performance, and improving evaluation methods for investigating surfactants. The results of this study will serve as a guide for academic purposes and help mining industry fields in the mitigation of coal dust impacts.